Back Cover: Charge‐Compensated Metallacarborane Building Blocks for Conjugation with Peptides (ChemBioChem 4/2016). (February 2016) - Frank, René; Ahrens, Verena M.; Boehnke, Solveig; Beck‐Sickinger, Annette G.; Hey‐Hawkins, Evamarie
Abstract : The back cover picture shows the selective internalisation of a novel imidazolium‐based charge‐compensated cobalt bis(dicarbollide) derivative conjugated to the Y1 receptor‐selective derivative of neuropeptide Y, [F 7, P 34 ]‐NPY. Receptor internalisation occurred within the same range as that observed for [F 7, P 34 ]‐NPY. These observations indicate that such conjugated peptides are promising candidates as boron‐delivering agents for boron neutron capture therapy (BNCT). More information can be found in the full paper by A. G. Beck‐Sickinger, E. Hey‐Hawkins et al. onpage 308 in Issue 4, 2016 (DOI:10.1002/cbic.201500569 ).